2004
DOI: 10.4049/jimmunol.173.3.1914
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses to Rhodococcus equi

Abstract: We examined innate immune responses to the intracellular bacterium Rhodococcus equi and show that infection of macrophages with intact bacteria induced the rapid translocation of NF-κB and the production of a variety of proinflammatory mediators, including TNF, IL-12, and NO. Macrophages from mice deficient in MyD88 failed to translocate NF-KB and produced virtually no cytokines in response to R. equi infection, implicating a TLR pathway. TLR4 was not involved in this response, because C3H/HeJ macrophages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 48 publications
3
52
1
Order By: Relevance
“…A recent study has identified TLR2 as the main receptor mediating the innate immune response of macrophages to R. equi [27]. Therefore, we investigated the expression of TLR2 and MyD88 mRNA in gal3 1/1 and gal3 À/À peritoneal macrophages.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent study has identified TLR2 as the main receptor mediating the innate immune response of macrophages to R. equi [27]. Therefore, we investigated the expression of TLR2 and MyD88 mRNA in gal3 1/1 and gal3 À/À peritoneal macrophages.…”
Section: Resultsmentioning
confidence: 97%
“…Gal3 À/À mice produce higher IL-12 levels than gal3 1/1 mice Based on the previous demonstration that galectin-3 regulates IL-12 production by APCs [29] and that R. equi is an efficient inducer of IL-12 and TNF-a production by macrophages [27], we measured the serum levels of both cytokines in gal3 1/1 and Immunohistochemical staining for galectin-3 in organs of R. equi-infected wild-type mice. Gal3 1/1 and gal3 À/À mice were intravenously inoculated with R. equi (1 Â 10 6 ), and splenic and liver immunohistochemical studies were performed at several intervals postinfection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations